2018
DOI: 10.1063/1.5052032
|View full text |Cite
|
Sign up to set email alerts
|

Local structure of stoichiometric and oxygen-deficient A2Ti6O13 (A = Li, Na, and K) studied by X-ray absorption spectroscopy and first-principles calculations

Abstract: Oxygen vacancy defects (VO) in Ti-based oxides play important roles in catalytic processes despite limited knowledge regarding their formation and characterization. Here, we demonstrate the use of X-ray absorption spectroscopy (XAS) measurements to compare the relative proportion of VO defects in as-grown alkali hexatitanate A2Ti6O13 (A = Li, Na, K). Both X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) regions were studied. The similarity of measured XANES spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
4
10
0
Order By: Relevance
“…The subtle differences in the microstructure of the materials obtained at lower temperature are responsible for the reversible insertion of at least two lithium ions (96 mA h g À1 ). According to our findings and recent firstprinciples calculations, [67] NTO-900 reveals a lower binding energy for twofold coordinated oxygen atoms in the tunnel structure, sitting next to the alkali ion. We suppose that this explains the higher electrochemical performance of the material.…”
Section: Electrochemical Performancesupporting
confidence: 80%
See 1 more Smart Citation
“…The subtle differences in the microstructure of the materials obtained at lower temperature are responsible for the reversible insertion of at least two lithium ions (96 mA h g À1 ). According to our findings and recent firstprinciples calculations, [67] NTO-900 reveals a lower binding energy for twofold coordinated oxygen atoms in the tunnel structure, sitting next to the alkali ion. We suppose that this explains the higher electrochemical performance of the material.…”
Section: Electrochemical Performancesupporting
confidence: 80%
“…The relative quantification of NTO-900 and NTO-1100 can be found in the Supporting Information (see Table S2, Supporting Information). These results-together with the changes seen in the Raman spectra (in Figure 5)-lead us to suppose a slight structural modification in the Ti-O sublattice when increasing the synthesis temperature of the NTO sample from 900 to 1100 C. In agreement with this, recent firstprinciples calculations [67] propose a low binding energy for twofold coordinated oxygen atoms in the tunnel structure, sitting next to the alkali ion. Their removal is thus energetically most favorable.…”
Section: Morphology Of the Nto Nanorodssupporting
confidence: 68%
“…Where symbols have their usual meanings and already been explained in our previous papers 14,[22][23][24] . It has been found that a ≠ b ≠ c, and also α = γ = 90 o ≠ β, as the case should be for monoclinic structure, here the value of β is decreasing on increasing the doping percentage of nickel.…”
Section: Results and Discussion X-ray Diffractionmentioning
confidence: 99%
“…Figure 8C shows the variation of half-life time (the time required for E′ to reduce to the middle between its initial and final values) with temperature. 58,59 Moreover, the potassium content in the (3 × 1) tunnel of K 2 Ti 6 O 13 is 2× higher than that in the (2 × 2) tunnel of K 1.36 Ti 8 O 16 . It is known that an increased number of migrating ions and an increased mobility result in an increased ionic conductivity.…”
Section: Temperature-dependent Electrical Transport Propertiesmentioning
confidence: 94%
“…As shown in Figure S10, K 1.36 Ti 8 O 16 contains a (2 × 2) tunnel with an area of 0.3 nm 2 , while K 2 Ti 6 O 13 involves a (3 × 1) tunnel with an area of 0.25 nm 2 . 58,59 Moreover, the potassium content in the (3 × 1) tunnel of K 2 Ti 6 O 13 is 2× higher than that in the (2 × 2) tunnel of K 1.36 Ti 8 O 16 . Hence, when compared to K 1.36 Ti 8 O 16 , it is more difficult for the potassium to transfer in K 2 Ti 6 O 13 .…”
Section: Temperature-dependent Electrical Transport Propertiesmentioning
confidence: 94%